A study on the morphological awareness of intermediate level adult Turkish EFL learners - Aydin, Fatma; Yildirim, Ozgur ((JELE) Journal Of English Language and Education, 2017)
The purpose of the current study was to investigate morphological awareness of a group of intermediate level adult Turkish EFL learners. The participants of this study were 168 Turkish first year university students who were taking intermediate level English courses at a state university in Turkey. Morphological Awareness Test (MAT) was the data collection instrument of the study. MAT consists of two sections: Sentence Completion and Word Relation. The Sentence Completion section consists of 27 multiple-choice test items with the purpose of understanding whether the participants are aware of the grammatical and lexical functions of some common derivational suffixes in English. In the Word Relation section, the participants were provided with a list of 20 word pairs (real words), and asked whether the second word in each pair comes from the first word or not. For analyzing the data, first the descriptive statistics (mean scores and standard deviations) were calculated for the sections of MAT and for individual suffixes, then the comparisons between the sections and among the participants were made by using paired-samples t-tests and one-way repeated measures ANOVAs. Results of the study indicated that intermediate-level adult Turkish EFL learners participating in the present study had moderate to high morphological awareness; they performed better in the Word Relation task than in the Sentence Completion task; and they showed the best performance in the verb making suffixes.